2005
DOI: 10.1152/ajpgi.00159.2004
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of CD40-CD40 ligand pathway inhibits the development of intestinal muscle hypercontractility and protective immunity in nematode infection

Abstract: In our previous studies, we demonstrated that during Trichinella spiralis infection, T helper (Th) 2 cells contribute to the development of intestinal muscle hypercontractility and worm expulsion from the gut via STAT6. In addition, we have linked the altered muscle contractility to the eviction of the parasite and thereby to the host defense. However, the initial events linking infection to the development of muscle hypercontractility are poorly understood. In this study, we examined the contribution of CD40-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 78 publications
0
25
1
Order By: Relevance
“…Ϫ/Ϫ mice also produce elevated levels of IL-4 and IL-5 after challenge, contradicting several studies which show that CD40/CD154 interactions are essential for the Th2 development caused by helminth infection (22,28,29,44) but supporting others (27).…”
Section: Discussioncontrasting
confidence: 65%
“…Ϫ/Ϫ mice also produce elevated levels of IL-4 and IL-5 after challenge, contradicting several studies which show that CD40/CD154 interactions are essential for the Th2 development caused by helminth infection (22,28,29,44) but supporting others (27).…”
Section: Discussioncontrasting
confidence: 65%
“…compared to those in uninfected mice. Previous studies have shown that Th2 cells play an important role in goblet cell response in intestinal nematode infections, including T. muris infection (3,28,29). In addition, recent studies have shown a role of TLR4 in goblet cell response in Citrobacter rodentium infection (30) and in differentiation of goblet cells in intestinal organoid and enterocyte cell cultures (31).…”
Section: Discussionmentioning
confidence: 99%
“…T. spiralis infection is a well accepted model of postinfectious IBS (Bercik et al, 2004;Wheatcroft et al, 2005). It has been widely used to study mechanisms underlying the motor changes induced by inflammation (Vallance et al, 1999;Torrents et al, 2002Torrents et al, , 2003Khan et al, 2005) and constitutes a good model to study the adaptation of the intestine to expel a clear cause of disease. Motor activity of the intestine is due to the activation of stereotyped motor behavior patterns accompanied by secretion and blood flow changes.…”
Section: Discussionmentioning
confidence: 99%